Application of lean manufacturing to improve the duct production process of an air conditioning company in the year 2021 - Salvador Reyes, Rebeca (2023)
The article's objective was the implementation of the lean manufacturing methodology in the production process of an air conditioning metal processing plant. For this, the methodology of 2 phases was used. The company and its current operation, structure, products, and work plan are presented in the first phase, demonstrating its main deficiencies. In phase 2, an improvement plan was made with lean manufacturing tools applied to the deficit of phase 1. As a result of the implementation of these tools, 64%, 80%, 71% and 50% of space in the measuring, cutting, bending, and welding stations, respectively, and an improvement in production times were obtained. Based on the study results, it is concluded that the application of lean manufacturing benefited the company by drastically improving its production process and work environment.